Systemic Risk Analysis Using Conditional Value at Risk (CoVaR) Model: Study of Conventional Banks in Indonesia - Rihana Sofie Nabella; Ghozali Maski; Setyo Tri Wahyudi (Universitas Negeri Malang, 2020)
This study aims to measure systemic risk in conventional commercial banks in Indonesia with the Conditional Value at Risk (CoVaR) model developed by Adrian and Brunnermeier (2009). The financial crises of 1998 and 2008 have become valuable lessons for Indonesian banks to always maintain financial system stability because the impact caused by systemic risks is very large. Systemic risk is the possibility of instability due to contagion in some or all of the financial system. This study uses a sample of 6 conventional commercial banks in Indonesia from January 2012 to December 2018. The results obtained from this study is the systemic risk is not related to the size of banks. Each bank has a negative externality so that it can cause a bank rush and systemic impact.